A review on robustness of covalent organic polymers for Co2 capture - Yaqub, S. (Trans Tech Publications Ltd, 2014)
The presence of carbon dioxide (CO2) in natural gas stream is a critical problem; besides causing corrosion it also reduces the energy contents and heating value of natural gas. Various separation techniques are available to separate CO2 from natural gas, such as metal organic framework (MOF), covalent organic framework (COF) and Covalent Organic Polymer (COP) adsorbents. The criteria of adsorbent selection that need to be fulfilled include high adsorption capacity, high selectivity of CO2 and hydrothermal stability at operating conditions. COPs are crystalline porous materials having high CO2 capacity and selectivity in the presence of water vapors. However, the research on COP material development is new and scarce information is available in literature. In this prospect, the paper highlights the different types of COPs, their basic constituents and the adsorption capacities. Â© 2014 Trans Tech Publications, Switzerland.